Long-term outcomes after endoscopic retrograde pancreatic drainage for symptomatic pancreaticojejunal anastomotic stenosis - Akihiko Kida (Nature Portfolio, 2021)
Abstract There is limited evidence supporting the usefulness of endoscopic retrograde pancreatic drainage (ERPD) for symptomatic pancreaticojejunal anastomotic stenosis (sPJS). We examined the usefulness of ERPD for sPJS. We conducted a retrospective analysis of 10 benign sPJS patients. A forward-viewing endoscope was used in all sessions. Following items were evaluated: technical success, adverse events, and clinical outcome of ERPD. The technical success rate was 100% (10/10) in initial ERPD; 9 patients had a pancreatic stent (no-internal-flap: n = 4, internal-flap: n = 5). The median follow-up was 920 days. Four patients developed recurrence. Among them, 3 had a stent with no-internal-flap in initial ERPD, the stent migrated in 3 at recurrence, and a stent was not placed in 1 patient in initial ERPD. Four follow-up interventions were performed. No recurrence was observed in 6 patients. None of the stents migrated (no-internal-flap: n = 1, internal-flap: n = 5) and no stents were replaced due to stent failure. Stenting with no-internal-flap was associated with recurrence (p = 0.042). Mild adverse events developed in 14.3% (2/14). In conclusions, ERPD was performed safely with high technical success. Recurrence was common after stenting with no-internal-flap. Long-term stenting did not result in stent failure. Clinical trial register and their clinical registration number: Nos. 58-115 and R2-9.